О СЕЗОННОЙ ДИНАМИКЕ ОБИЛИЯ ГРЕБНЕВИКОВ В РАЙОНЕ СЕВАСТОПОЛЯ - (:unkn) unknown (My University, 2012)
Отмечены существенные изменения в таксономической и размерной структуре мезопланктона и желетелого макропланктона (смещение сроков появления, размножения и доминирования разных видов, преобладание более крупных особей большую часть года) как следствие повышения температуры воды в 2009 г. Кроме температурных условий развитие планктона в прибрежных водах Севастополя определяется наличием хищников и состоянием кормовой базы.
ABOUT SEASONAL DYNAMICS OF CTENOPHORES ABUNDANCE NEAR SEVASTOPOL
As a consequence of higher water temperatures in 2009 year, the significant changes in taxonomic and size structure mesoplankton and gelatinous macroplankton (the shift of period appearance, reproductions and dominance of different species, predominates larger individuals the most part of the year) were made. In addition to the temperature conditions, the plankton development in the coastal water of Sevastopol is determined by the presence of predators and availability of food.
Keywords: мезопланктон; макропланктон